Strategic communication for startups and entrepreneurs in China - Men, Linjuan Rita; Ji, Yi Grace; Chen, Zifei (Milton Park, Abingdon, Oxon ; New York : Routledge, 2020)
"This book presents a comprehensive guide for public relations and communication professionals and entrepreneurs to effectively manage the communication aspects of startups in the context of business in China. Drawing on interdisciplinary theories, current issues, and updated research evidence obtained from entrepreneurs and startup leaders in China, this concise volume provides research-based insights on the best practices for public relations and communication management in the unique context of startups. It addresses relationships with stakeholders, public relations practice, leadership communication, and how to leverage the power of social media in the entrepreneurial context. Strategic Communication for Startups and Entrepreneurs in China will be of great benefit to public relations and strategic communication scholars and practitioners, startup leaders and entrepreneurs interested in opportunities in China, as well as advanced students in public relations, business communication, and entrepreneurship"--
Why startup strategic communication? -- The state of startups and entrepreneurship in China -- Understanding the stakeholders of startups -- The functions of public relations in startups -- Cultivating stakeholder relationships for startups -- Building an effective startup culture -- Entrepreneurial leadership communication -- Social media communication strategies for startups -- Best practices of startup strategic communication.
OCLC-licensed vendor bibliographic record.
Keywords: Business communication -- China; Public relations -- China; BUSINESS & ECONOMICS / Public Relations; BUSINESS & ECONOMICS / Entrepreneurship; LANGUAGE ARTS & DISCIPLINES / Communication